2008 IEEE International Conference on Software Maintenance 2008
DOI: 10.1109/icsm.2008.4658058
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic slicing of multithreaded programs for race detection

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Our current work that generalizes our approach to handle multithreading bugs is inspired by several key observations taken from prior work. The first of these comes from Tallam et al work on extending dynamic slicing to capture data race bugs [11]. In this work, the authors observed that dynamic slicing traditionally considers only RAW data and control dependencies, and this may result in dynamic slices failing to capture relevant data race bugs in an execution.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Our current work that generalizes our approach to handle multithreading bugs is inspired by several key observations taken from prior work. The first of these comes from Tallam et al work on extending dynamic slicing to capture data race bugs [11]. In this work, the authors observed that dynamic slicing traditionally considers only RAW data and control dependencies, and this may result in dynamic slices failing to capture relevant data race bugs in an execution.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 2 shows the pseudocode for this on-the-fly approach for detecting data races. This accounts for the observation by Tallam et al [11] that data races can be represented by either RAW, WAR, or WAW dependencies. Note that in Figure 1, the checking for RAW data races is done on-the-fly while also performing the suppression.…”
Section: Data Race Bugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In lines 11-15, the algorithm adds a dependence d to the slice and the work list, if d is a value difference or a flow difference. Otherwise, the algorithm handles def-use differences by adding the dependence d to the slice if the dependence d ′ corresponding to d in the passing run does not align with d (lines [16][17][18][19][20][21]. Observe that though d is added to the slice it is not placed in the work list.…”
Section: Inputmentioning
confidence: 99%
“…Many static and dynamic analysis techniques [32], [33], [44] can be classified as model-based debugging as well. Although few model-based techniques have employed the concept of failure association, incorporating association measures and other statistical analyses into program models can be a future direction for improving the performance of model-based debugging techniques.…”
Section: A Fault Localizationmentioning
confidence: 99%